Case report: Partial visual recovery from incomplete traumatic optic nerve avulsion caused by a badminton shuttle - Yuto Kawamata; Yuta Kitamura; Hirotaka Yokouchi; Takayuki Baba (American Journal of Ophthalmology Case Reports, 2022)
Purpose: Blunt ocular trauma rarely results in optic nerve avulsion. Here, we report a case of incomplete optic nerve avulsion caused by the impact of a badminton shuttlecock. Observations: The patient was a 16-year-old healthy male. A badminton shuttlecock hit his right eye from a short distance. On his first visit to the local eye clinic, his visual acuity in the right eye was hand motion. About 4-mm hyphema in height was observed in the right eye. Three days after the injury, visual acuity improved to 20/50, but the intraocular pressure increased to 40 mmHg; hence, intraocular pressure (IOP)-lowering medication was initiated. Five days after the injury, although hyphema had decreased gradually, he noticed a worsening of vision and was referred to our department. In his right eye, visual acuity was reduced to finger-counting, IOP was 38 mmHg. Slit-lamp examination of the right eye revealed a dilated pupil, hyphema, and angle recession. Fundus examination revealed dilation of the central retinal vein and edematous changes around the optic nerve head. Optical coherence tomography showed a very deep depression of the optic nerve head and partial rupture of the optic nerve axons. B-mode ultrasonography showed hypolucency just posterior to the optic nerve head. Goldmann perimetry revealed a central visual field defect in the right eye. Computed tomography showed no signs of optic canal fracture. These findings suggest that incomplete optic nerve avulsion had occurred. We performed IOP-lowering and anti-inflammatory therapy. After treatment, visual acuity was restored to 20/50, and the deep depression of the optic nerve head recovered to an almost normal range. Conclusion and Importance: It was assumed that the impact of the badminton shuttlecock caused irreversible changes in the optic nerve head, but the visual function partially improved with IOP-lowering and anti-inflammatory therapy. Because eye injury in badminton can cause severe damage to visual function, every badminton player needs to wear an appropriate eye shield, and rules or guidelines to prevent untoward accidents are needed in badminton.